ASSESSING THE IMPACT ON PEFR AMONG SMOKERS AND PASSIVE SMOKERS–A COMPARATIVE STUDY - B., GANESH PANDIAN; P., SIREESHA; N. G., YEN PING; G., SUSMITHA; T., SAM AASEER (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: The purpose of this study was to monitor the intensity and difference in Peak Expiratory Flow Rate (PEFR) between smokers and passive smokers. Methods: A total of 1000 participants were enrolled in two groups as smokers and passive smokers who are living closely with smokers. Their PEFR values were measured with Wright’s mini peak flow meter. The influence of smoking on the lung function among smokers and passive smokers were assessed with a suitable statistical test. Results: Among the study participants, most of the smokers were in the age group of 31 to 60 and 31 to 50 in passive smokers. Based on the lung function smokers (31%) and passive smokers (19.2%) were in the red zone, PEFR was decreased in both smokers as well as passive smokers, and the magnitude of decline was higher in passive smoking elderly individuals. The impact of passive smoking was significantly observed in all the categories of smoking history they are living with. Conclusion: Smokers and passive smokers have equally deleterious effects on PEFR. Where passive smoking emerged as the main variable to influence airway obstruction in smokers that caused a greater reduction in PEFR.